2020
DOI: 10.1111/phn.12779
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of faith‐based residential addiction recovery for the homeless

Abstract: Objective To examine the economic and fiscal impact of a faith‐based long‐term residential addiction recovery program for homeless men on the state and local economy. Design This descriptive study used entry, within‐program, and exit data to determine the program's fiscal and economic impact. Sample The population consisted of 5,122 homeless men at an inner‐city mission in Baltimore City from 2006 to 2019. Measurements To compare costs and savings at different program intervals, economists examined program dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…An impact evaluation study to assess the financial impact of a faith-based long-term residential addiction recovery intervention, the Mission, in Baltimore, Maryland, revealed that every person who participates in the Mission for a year saves the state and county governments $14, 263. These savings result from less spending on health care, social services, and criminal justice utilization ( 28 ). The study participants comprised 5,122 homeless men recovering from substance use disorder from 2006 to 2019.…”
Section: Discussionmentioning
confidence: 99%
“…An impact evaluation study to assess the financial impact of a faith-based long-term residential addiction recovery intervention, the Mission, in Baltimore, Maryland, revealed that every person who participates in the Mission for a year saves the state and county governments $14, 263. These savings result from less spending on health care, social services, and criminal justice utilization ( 28 ). The study participants comprised 5,122 homeless men recovering from substance use disorder from 2006 to 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Data from this study validated the economic impact of the Mission's programs on cost savings and revenue generation to state and local governments. Over the years, this data has been leveraged to further develop stakeholder partnerships among local politicians, businesses, government, and community leaders (Lashley, 2020).…”
Section: Sustainability: a Framework For Analysismentioning
confidence: 99%
“…Biblical discipleship, relapse prevention, mental health counseling, work therapy, and substance abuse treatment are integrated with wrap around services to provide a holistic approach to addiction treatment. Wrap around supportive services include on‐site primary and behavioral health care, specialty care including comprehensive dental care, educational, workforce development, and life enrichment programs, and legal and social services (Lashley, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The CDC recommends a "whole community" (CDC, 2020, p. 1) approach to addressing the threat of COVID-19 among persons experiencing homelessness (CDC, 2020) (Lashley, 2020).…”
Section: Introductionmentioning
confidence: 99%